Evaluation and comparison of the microbial consortia enriched by gamma-caprolactone and N-Acyl homoserine lactones for effective quorum sensing disruption - Xu, Boyan (ELSEVIER SCI LTD, 2021)
10.1016/j.ibiod.2021.105200